Strategies for Sustainable Urban Development—Addressing the Challenges of the 21st Century - Liyin Shen; J. Jorge Ochoa; Haijun Bao (Buildings, 2023)
Urbanisation has been one of the most transformative processes of our time, and in recent decades has led to significant changes in the way we live, work, and interact with the world around us [...]